The association between high atherogenic index of plasma and impaired lung function: a population-based study - Liang Yang; Yuanzhou Wu; Ling Chen; Zizhao Li; Wenfei Zhu; Ziyan Zhang; Hui Li; Yang Huang; Qunqing Chen (Frontiers in Medicine, 2025)
ObjectiveAlthough AIP is a recognized cardiovascular risk marker, its association with pulmonary function and sex-specific differences remains unclear. This study investigated whether elevated AIP is independently associated with reduced lung function and examined potential sex-specific patterns.MethodsData from 4,565 participants in the NHANES 2007–2012 dataset were analyzed using a cross-sectional design. AIP served as the exposure variable, with five lung function metrics (including FEV1, FVC, and FEV1/FVC ratio) as outcomes. Weighted multiple linear regression, threshold effect analysis, subgroup comparisons, and XGBoost modeling were performed to assess associations.ResultsMultivariable regression showed a significant negative association between AIP and FEV1 (β = −121.3 mL/unit, p < 0.001) and FVC (β = −147.1 mL/unit, p < 0.001), with no significant link to FEV1/FVC ratio. Subgroup analysis revealed a U-shaped non-linear association in females, with inflection points at AIP values of 0.77 (FEV1) and 0.78 (FVC), beyond which declines in lung function plateaued. Males exhibited a consistent negative correlation across all AIP levels.ConclusionElevated AIP is independently associated with reduced lung function, particularly non-linear effects in females. These findings support AIP as a potential adjunct marker for pulmonary function assessment in clinical practice.